The role of neuregulin-1 in the response to nerve injury. - Fricker, F; Bennett, D (2011)
Axons and Schwann cells exist in a highly interdependent relationship: damage to one cell type invariably leads to pathophysiological changes in the other. Greater understanding of communication between these cell types will not only give insight into peripheral nerve development, but also the reaction to and recovery from peripheral nerve injury. The type III isoform of neuregulin-1 (NRG1) has emerged as a key signaling factor that is expressed on axons and, through binding to erbB2/3 receptors on Schwann cells, regulates multiple phases of their development. In adulthood, NRG1 is dispensable for the maintenance of the myelin sheath; however, this factor is required for both axon regeneration and remyelination following nerve injury. The outcome of NRG1 signaling depends on interactions with other pathways within Schwann cells such as Notch, integrin and cAMP signaling. In certain circumstances, this signaling pathway may be maladaptive; for instance, direct binding of Mycobacterium leprae onto erbB2 receptors produces excessive activation and can actually promote demyelination. Attempts to modulate this pathway in order to promote nerve repair will therefore need to give consideration to the exact isoform used, as well as how it is processed and the context in which it is presented to the Schwann cell.